Impact of renewable energy utilization and artificial intelligence in achieving sustainable development goals - Hannan M.A.; Al-Shetwi A.Q.; Ker P.J.; Begum R.A.; Mansor M.; Rahman S.A.; Dong Z.Y.; Tiong S.K.; Mahlia T.M.I.; Muttaqi K.M. (Elsevier Ltd, 2023)
Artificial intelligence; Energy policy; Environmental protection; Planning; Sustainable development; Elicited expert; Energy mix; Exponential growth; Global energy; Impact analysis; IS planning; Renewable energies; Renewable energy use; Sharp increase; Sustainable development goal; Energy utilization